Hydrothermal liquefaction of demineralized wastewater algae biomass - Carpio, Rowena B.
Microalgae are considered a potential resource for the production of biofuels and chemicals due to their high biomass productivity and ability to grow in any water environment including wastewater. However, microalgae biomass harvested from wastewater typically contain high ash (30-50%), which reduces the conversion efficiency and quality of resulting fuel products. This study provided a scientific justification for the development of demineralization pretreatment to improve the conversion of wastewater algae biomass to biocrude oil via the HTL process. The wastewater algae (WA) biomass was subjected to different demineralization pretreatments by leaching, using deionized water (Dl-H20) and different dilute-acid solutions: acetic acid (AA), formic acid (FA), and sulfuric acid (SA). The ash removal efficiency of different pretreatments and their impact on biomass in terms of the physical structure, chemical composition, and thermal decomposition behavior were evaluated. The performance of demineralization was evaluated under HTL, and the most suitable pretreatment was identified in terms of the biocrude oil yield and energy recovery. After which, the effects of the operating parameters, including the reactor initial headspace pressure, feedstock load ratio, reaction temperature and reaction time on the HTL product yields and/or bio-crude oil quality were investigated. An energy balance using energy consumption ratio (ECR) was calculated to compare the energy required for HTL conversion against the energy that can be recovered from biocrude oil obtained by combustion while accounting for combustion energy loss and heat recovery. This study successfully demonstrated the potential of improving the biocrude yield of WA biomass by demineralization pretreatment. Among the pretreatments employed. FA was the most effective in removing ash from WA biomass with about 35.86% removal efficiency, followed by SA and then AA with 26.25% and 25.0I %, respectively. Pretreatment with DI-H20 was the least effective with only 2.94% removal efficiency. Demineralization using dilute-acids were accompanied by an increase in higher heating value (HHV) and led to a more complicated thermal decomposition behavior under an inert condition, leaving a higher fraction of the volatile solid as char. Conversely, the average apparent activation energy of the biomass was effectively reduced after the FA and SA treatment, while there was no significant effect using AA. Demineralization significantly improved the biocrude oil yield by 23-49%, compared to that of untreated biomass with only 17.01 %daf (dry, ash-free basis). Demineralization did not improve the HHV of the generated biocrude oil, but it does increase the ER of the biocrude oil, the highest value (41.83 ± 1.87%) was obtained from the FA-treated biomass. The chemical composition of the biocrude oil obtained from demineralized biomass contained less than/equal abundance in hydrocarbons, N&O heterocycles, and oxygenates; and the simulated boiling point distribution showed the biocrude oil derived from demineralized biomass contained lesser amounts of light and medium boiling material (<300°C) which is about 43%, compared to untreated biomass which has 47%. Overall, the quality of biocrude oil generated from different demineralized biomass were fairly similar, however, on the basis of biocrude oil yield and energy rec-0very and ash removal efficiency, FA-treatment was found to be the most suitable demineralization pretreatment for the HTL of wastewater algae biomass. The HTL of demineralized biomass at increasing reactor initial headspace pressure contributed in the increase of the system pressure during the HTL process, while biocrude oil yield decreased, in favor of the solid residue. Meanwhile, increasing the feedstock load ratio showed no significant influence on the biocrude oil yield, its effect was most pronounced in the decrease of gas product yield. At four levels of reaction temperature and reaction time, a maximum biocrude oil yield of about 26 %daf was obtained at several conditions, with the least severe condition identified as 280°C and 60 min. The HHV of the biocrude oil from demineralized biomass tend to increase with increasing temperature at different reaction time. The ECR showed a net energy gain for the biocrude oil obtained via the HTL process, with lowest ECR obtained at 280°C and 60 min. The reaction network developed for the HTL of demineralized biomass based on the GC-MS analysis of the biocrude oil and aqueous phase product, as well as some inputs from the literature, showed a complex network of chemical reaction and distribution network of the chemical group to different HTL product streams. With the negligible concentration of crude lipid in the original biomass, the proposed network indicated a possible "Fischer-Tropsch type" reaction for the formation of long-chain hydrocarbons detected in the biocrude oil samples. A kinetic model based on the lumped of the products fraction dependably correlated the experimental results from the HTL of demineralized wastewater algae biomass. A sensitivity analysis for the HTL product yield at 280°C showed that the yield of the aqueous-phase products was less sensitive to changes in the rate constant than were the yields of residual solids, biocrude oil, and gaseous products. Analysis also revealed that the rate constant Ki, which is related to the conversion of solid to aqueous phase, was the rate limiting pathway that controls the conversion of demineralized bio